Selected Filipino brides' buying behavior for ready-to-wear bridal gowns - Baldazo, Ivy L.
Ready-to-wear bridal gowns has been around for some time, but is still considered a new concept by many. Modern brides opt for ready-to-wear for various reasons. This study aimed to analyze the buying behavior of selected Filipino brides in relation to their ready-to-wear bridal gown. Specifically, the study aimed to identify different factors that influence the choices of Filipino brides in buying their ready-to wear bridal gowns. The study also aimed to discover if Filipino women still follow Filipino wedding traditions and superstitions (pamahiin), which are considered an integral part of Filipino culture. Literature on weddings in the Philippines from journals, books, theses, and online sources were used to gather data on Filipino wedding traditions and superstitions. The data gathered from interviews and survey among thirty-one (31) purposively selected respondents who opted for ready-to-wear bridal gowns were used to determine the factors in buying ready-to-wear bridal gown. Other influences, problems, and issues encountered by these brides were also discussed.According to the results of the study, it was evident that family traditions and superstitions do not influence the decision of the respondents in choosing ready-to-wear bridal gowns. Family, friends, price, time constraints were the external factors; while fit, comfort, and style were the internal factors considered by the participants as affecting their buying considerations for their ready-to-wear bridal gown.t is recommended to use larger sample population for the survey to achieve a more conclusive study. Other locations such as the provinces may be studied for better comparison. Other demographic parameters such as religion and interracial marriages may also be studied to get a better scope on the traditions and superstitions.